2005
DOI: 10.1021/jp045715t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Solvation and Rotational Relaxation of Coumarin 153 in Ionic Liquid Confined Nanometer-Sized Microemulsions

Abstract: The effects of confinement of the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate on solvation dynamics and rotational relaxation of Coumarin 153 (C-153) in Triton X-100/cyclohexane microemulsions have been explored using steady-state and picosecond time-resolved emission spectroscopy. The steady-state and rotational relaxation data indicate that C-153 molecules are incorporated in the core of the microemulsions. The average rotational relaxation time increases with increase in w ([bmim][BF(4)]/[TX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 63 publications
1
129
0
Order By: Relevance
“…Keywords: dynamic light scattering · ionic liquids · IR spectroscopy · microemulsions · NMR spectroscopy · UV/Vis spectroscopy [27] More recently, a study by us has indicated that the interaction between the electronegative oxygen atoms of the oxyethylene (OE) units of TX-100 and the electropositive imidazolium rings may be the driving force for the solubiliza- 4 ] into the core of the TX-100 aggregates. [28] These nonaqueous IL microemusions are a new class of reaction media.…”
Section: Abstract: the Ionic Liquid (Il) 1-butyl-3-methylimidazolium mentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: dynamic light scattering · ionic liquids · IR spectroscopy · microemulsions · NMR spectroscopy · UV/Vis spectroscopy [27] More recently, a study by us has indicated that the interaction between the electronegative oxygen atoms of the oxyethylene (OE) units of TX-100 and the electropositive imidazolium rings may be the driving force for the solubiliza- 4 ] into the core of the TX-100 aggregates. [28] These nonaqueous IL microemusions are a new class of reaction media.…”
Section: Abstract: the Ionic Liquid (Il) 1-butyl-3-methylimidazolium mentioning
confidence: 99%
“…[26] Also, microemulsions with ILs as the polar core dispersed in a continuous oil phase by a suitable surfactant may have some unknown properties and some potential applications owing to the unique features of ILs and microemulsions. [25,27] Despite their great potential, reports on the nonaqueous IL microemulsions, in particular on their microstructures, are still very scarce. Herein, we study the nonaqueous microemulsions of TX-100 in benzene with polar [bmim]A C H T U N G T R E N N U N G [BF 4 ] as a water substitute.…”
Section: Abstract: the Ionic Liquid (Il) 1-butyl-3-methylimidazolium mentioning
confidence: 99%
“…A swelling behavior of the IL nanodomains with increasing R value was observed consistent with the observations of Gao et al The SANS curves with the corresponding fits for ellipsoidal structures are illustrated in Figure 2. By contrast, the extracted sizes were in the typical range of aqueous microemulsions arguing strongly against the DLS radii reported by Gao et al The solvation dynamics and rotational relaxation of Coumarin 153, a rigid molecule having a single low-lying excited state and simple solvatochromic behavior (Maroncelli & Fleming 1987) has been investigated for the same system by Chakrabarty et al (Chakrabarty et al, 2005). With steady state and time resolved fluorescence spectroscopy measurements at different R values they observed a red shift in the emission spectra with increasing [bmim] [BF 4 ] content indicating the formation of RTIL pools.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 50%
“…. By comparing the results from previous studies Chakrabarty et al 2005) with the results obtained in Figure 1, a large amount of IL can be solubilized in emulsions using much lower weight fractions of the mixture of Tween 80 ® and Span 80 ® surfactants. These can be explained in terms of interfacial properties provided by the mixtures of two different nonionic surfactants that are more favourable.…”
Section: Pseudo-ternary Phase Diagrams Of the Emulsionsmentioning
confidence: 67%